Untargeted Metabolomic Profiling, Multivariate Analysis and Biological Evaluation of the True Mangrove (Rhizophora mucronata Lam.) - Nabeelah Bibi Sadeer; Gabriele Rocchetti; Biancamaria Senizza; Domenico Montesano; Gokhan Zengin; Ahmet Uysal; Rajesh Jeewon; Luigi Lucini; Mohamad Fawzi Mahomoodally (MDPI AG, 2019)
Currently, there is a renewed interest towards the development of plant-based pharmacophores. In this work, 16 extracts prepared from the leaves, twigs, roots and fruits of a hydro-halophyte, Rhizophora mucronata Lam. (Family: Rhizophoraceae), were studied for possible antioxidant activity and the phenolic profiles established. Thereafter, enzymatic inhibitory activities (α-amylase, α-glucosidase, tyrosinase, acetyl- (AChE), butyrylcholinesterase (BChE), lipase, and elastase) were assessed. The total phenolic, flavonoid, phenolic acid, tannin, flavanol and triterpenoid content were estimated using standard assays. An untargeted metabolomics-based approach, based on ultra-high-pressure liquid chromatography coupled to quadrupole-time-of-flight mass spectrometry (UHPLC-QTOF-MS) followed by multivariate statistics, was then used to comprehensively profile and describe the phenolics present. UHPLC-QTOF-MS allowed for putatively annotating 104 phenolic acids, 103 flavonols, 94 flavones, 71 anthocyanins, 66 tyrosols, 29 lignans, 15 alkylphenols and 10 stilbenes in the extracts. Nine strains (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Methicillin-resistant Staphylococcus aureus (MRSA), Salmonella enteritidis, Sarcina lutea, Proteus mirabilis, Bacillus cereus and Candida albicans) were then used to investigate the antimicrobial properties. The methanolic twig extract exhibited significant reducing potential towards Cu (II)/Cu (I) and Fe (III)/Fe (II) (1336.88 ± 15.70 and 710.18 ± 21.04 mg TE/g, respectively) and was the most potent DPPH radical scavenger (807.07 ± 6.83 mg TE/g). Additionally, the methanolic twig extract showed significant inhibition against most targeted enzymes. Anti-microbial results showed that all extracts were active against MRSA. Multivariate analysis demonstrated that the phenolic profile of ethyl acetate extracts and leaves were the two most discriminative parameters in terms of solvents and organs, respectively. The present findings indicated that R. mucronata may be further explored for the management/prevention of oxidative stress, neurodegenerative complications and hyperpigmentation.